O ensino de química para surdos: produção de planos de aula especializado para turmas inclusivas - Marques, Ronaldo Henrique Souza (2018)
The present work aims to propose the creation of Specialized Classroom Methods (SCM) for deaf students, so that it is possible to strengthen the bonds between teachers and interpreters and to provide students with a better understanding of the chemical content. The creation of the SCM’s showed that for the teaching of inclusive classes of deaf students it is necessary to denote aspects inherent to the deaf culture, such as more imagistic classes, more phenomena and even adaptations of scientific terms that will allow a better understanding of what is being studied. It is concluded that the main key for a better development of inclusive classes is the communication between teacherinterpreter, since the communication channel between these parts improves the teacher understands the function of the interpreter, and the interpreter knows the objective of the teacher. Within the proposed creation of model plans, to analyze the learning mode of deaf students, from the point of view of interpreters and teachers, aiming to understand the failures in learning mechanisms and propose, within the SCM, new structures to reduce the learning gap of deaf students and listeners.